The Reconstruction of Indonesian Education Through Ki Hajar Dewantara’s Concept of Reasoning of the Liberated Human - Munawar, Raja Maulana Syahid; Ramadhani, Muhammad Alif; Zayn, Muhammad Fauzan Salmaan; Al Asy’ari, M. Khoirul Hadi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The Indonesian education system faces a crisis rooted in the loss of a philosophical direction that should liberate student thinking. This paper examines Ki Hajar Dewantara’s concept of Nalar Manusia Merdeka (Reasoning of the Liberated Human) as a transformative epistemological foundation for reconstructing Indonesian education. Employing a qualitative approach with library research and content analysis of Dewantara’s writings, particularly Menuju Manusia Merdeka, this study explores its historical and conceptual dimensions. The findings indicate that Dewantara’s epistemology signifies a paradigmatic shift from colonial education, promoting a framework that integrates empirical observation, rational thinking, and local cultural consciousness. His Tripusat Pendidikan (Three Centers of Education: family, school, community) presents a holistic solution to educational fragmentation. Furthermore, Dewantara’s concept of freedom extends beyond political liberation to encompass intellectual and cultural emancipation, fostering autonomous yet socially responsible individuals. This research concludes that Nalar Manusia Merdeka offers an essential philosophical basis for developing an Indonesian education system that is liberating, culturally authentic, and globally competitive.